Pelatihan Editing Video Menggunakan Aplikasi Capcut Untuk Meningkatkan Keterampilan Guru Dalam Editing Video - Alfathoni, Muhammad Ali Mursid; Sya’dian, Triadi; Azizah, Azizah; Purba, Rinanda (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
In the digital era, video editing skills have become an essential competency for teachers to enhance the learning process. These skills enable teachers to create more interactive and engaging educational videos. However, not all teachers possess adequate video editing abilities. Therefore, this training activity aimed to improve the video editing skills of teachers at SMP Citra Harapan using the CapCut application. The training was conducted through a combination of theoretical and practical sessions, encompassing three main stages: preparation, implementation, and evaluation. The results indicated that all participants enthusiastically participated in the training, effectively understood the materials, and successfully applied video editing skills in practice. This training is expected to support teachers in producing more effective and creative educational videos.